Parental Control System for Children on Wireless Network - Wan Ismail, Wan Hazimah (Journal of Computing Technologies and Creative Content, 2020)
Today’s teenagers, and school age children are getting more and more technologically sophisticated, very often outpacing what their parents know about these high-tech gadgets. While for some kids that actually means that they are learning computer languages, creating websites, and even building robots, most others are simply using today’s technology to watch videos on YouTube and play MMORPGs (massively multiplayer online role-playing games) or they are talking on their cell phones and sending text messages. Unfortunately, many of the things kids can do online and with their cell phones can lead to a lot of trouble if they are not monitored. From watching porn and other inappropriate video and websites to sexting (sending inappropriate text messages or photographs) and chatting with predators, new technology can lead to new problems. Cell phones and the internet have even led to new ways for kids to be bullied or cyber bullying. That does not have to mean that kids cannot have a computer or cell phone, but we should learn about parental controls that can help protect them as they use the latest high-tech gadgets. The aim of this project is to develop the parental control system that able to monitor the children’s behavior and to block the inappropriate website. This system also has time management to manage the surfing time access the internet.